IJAR 2020
DOI: 10.36106/ijar/5702413
|View full text |Cite
|
Sign up to set email alerts
|

Sex Knowledge and Attitude Among Undergraduate Medical Students: A Cross-Sectional Study

Abstract: Background: The word ‘sex’ in India is a taboo and not discussed openly. Sex attitude referes to one’s attitude toward sexuality or different sexual behaviors such as masturbation, oral sex, anal sex and sexual relationships. Poor sex knowledge causes many of these problems. Liberal attitude without adequate knowledge is harmful. Aims: The present study aimed to assess the knowledge and attitude of undergraduate medical students. Methods: a cross sectional study was carried out to assess sex knowledge and atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Furthermore, our study found that a significant proportion of participants had been using the whitening cream for less than 6 months (31.04%), suggesting a relatively short-term usage duration. This is consistent with the transient nature of whitening cream usage, as individuals may discontinue or switch products based on perceived effectiveness (Kumar et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, our study found that a significant proportion of participants had been using the whitening cream for less than 6 months (31.04%), suggesting a relatively short-term usage duration. This is consistent with the transient nature of whitening cream usage, as individuals may discontinue or switch products based on perceived effectiveness (Kumar et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…With their aging, the sexual knowledge gains of students are increasing. Avci et al (2016) showed that the first-and fourth-grade ranges are significant and the findings of Sidi et al (2013) were consistent with Kumar et al (2020). These results can be explained as students gaining more knowledge and clinical information in the increasing academic year.…”
Section: Discussionmentioning
confidence: 52%
“…The results also show that the earlier it happened, the higher their knowledge and this could be linked to their interest and their understanding of previous sexual behavior (Baumeister, 2000;Zhang et al, 2010) and the degree of knowledge is different between urban and rural areas (Lou et al, 2012;McMann and Trout, 2021). In a study with 752 medical undergraduate students in different universities in India, by Kumar et al (2020), the results showed that the participants are deficits in sexual knowledge and conservative attitude in certain areas. Females, higher education level, and urban area participants have higher sexual knowledge and liberal attitude.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations